PERBANDINGAN FIELD STRENGTH UPPER DAN COMBINED ANTENNA PADA TRANSMISI TV 7 SURABAYA - Surjati, Indra; Setyaningsih, Endah; Hermawan, Stevanie (Universitas Tarumanagara, 2006)
It has been well known that TV 7 one of TV stations in Indonesia always provides good quality of program for its clients throughout national frameworks from its head quarter in Surabaya. Field strength antenna plays important role in this service, especially its prominent parameters like antenna gain, radiation pattern as well as its radiated powers. It has been noted from this investigation that upper antenna suits for the above purpose.